STRATEGI PENGEMBANGAN PRODUK KAIN TENUN IKAT SINTANG - Lisyawati Nurcahyani (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2018)
enun ikat Sintang is one of the traditional products whose existence is threatened with extinction. The purpose of this study explains how Sintang community’s strategies and local governments respond to these threats through policy and cooperation in the development of weaving products. This study used library method and field observations. Interviews were conducted with artisans, private organizations (NGO) and local governments. The results of this study were variety of efforts such as the development of human resources artisans, provision of raw materials, product diversification, the provision of the means of production and marketing. In order for this strategy to work well it needed the intervention of authorities and institution such as non-governmental organizations such and the local government. Despite efforts towards the developmen had been done, the problems still remain especially in the supply of raw materials on natural resources in the forest as well as marketing as the effect of high production costs that make the Ikat weaving more expensive. AbstrakTenun Ikat Sintang merupakan salah satu produk tradisional yang keberadaannya terancam punah. Tujuan penelitian ini menjelaskan bagaimana strategi masyarakat Sintang dan pemerintah daerah merespon ancaman ini melalui kebijakan dan kerja sama dalam pengembangan produk tenun ikat. Penelitian ini menggunakan metode kualitatif dengan melakukan wawancara dan pengamatan di lapangan serta didukung dengan studi kepustakaan. Subyek penelitian adalah para perajin, lembaga swadaya masyarakat, dan Pemerintah Daerah. Hasil penelitian menunjukkan bahwa strategi yang dilakukan berjalan dengan baik dan diperlukan keterlibatan pihak lain seperti yayasan dan Pemerintah Daerah. Walaupun pengembangan telah dilakukan, masih ada hambatan yang belum terselesaikan terutama dalam penyediaan bahan baku dari tumbuh-tumbuhan alam yang ada di hutan dan dalam bidang pemasaran yang disebabkan tingginya biaya produksi sehingga membuat harga tenun ikat menjadi mahal.